A Forecast Combination Framework with Multi-Time Scale for Livestock Products' Price Forecasting. (20th October 2019) - Ling, Liwen; Zhang, Dabin; Mugera, Amin W.; Chen, Shanying; Xia, Qiang
Abstract : China's livestock market has experienced exceptionally severe price fluctuations over the past few years. In this paper, based on the well-established idea of "forecast combination, " a forecast combination framework with different time scales is proposed to improve the forecast accuracy for livestock products. Specifically, we combine the forecasts from multi-time scale, i.e., the short-term forecast and the long-term forecast. Forecasts derived from multi-time scale introduce complementary information about the dynamics of price movements, thus increasing the diversities within the modeling process. Moreover, we investigate a total of ten combination methods with different weighting schemes, including linear and nonlinear combination. The empirical results show that (i) forecast performance can be remarkably improved with this novel combination idea, and short-term forecast model is more suitable for the products with a relatively high volatility, e.g., mutton and beef; (ii) geometric mean, which provides a nonlinear combination, is the most effective one among all the combination methods; and (iii) variance-based weighting scheme can yield a superior result compared to the best individual forecast, especially for the products such as egg and beef.